Application of full-neuroendoscopic technique in surgical treatment of posterior cranial fossa lesions - ZHOU Zhiyi; ZHAO Hao; MIAO Yifeng; ZHU Chihao; YANG Xi; WANG Siyuan; FENG Junfeng; QIU Yongming (Shanghai Jiaotong Daxue xuebao. Yixue ban)
Objective·To investigate the application effects and benefits of full-neuroendoscopic technique in the surgical treatment of posterior cranial fossa lesions.Methods·A retrospective analysis was conducted on the clinical data of 105 patients with posterior cranial fossa lesions who underwent surgery using full-neuroendoscopic techniques at the Department of Neurosurgery, Renji Hospital, Shanghai Jiao Tong University School of Medicine, between January 2021 and December 2023. The data included patients′ gender, age, lesion locations, nature of lesions, surgical procedures, and postoperative recovery. Follow-up with contrast-enhanced MRI was performed one month postoperatively, with subsequent follow-ups every three months on average, depending on the nature of the lesions.Results·Among the 105 patients, there were 45 males with an average age of (56±17) years and 60 females with an average age of (62±12) years. Lesions were predominantly located in the cerebellopontine angle area (78 cases), with others in the petrous bone area (7 cases), cerebellum (10 cases), and brainstem (10 cases). The nature of lesions included vestibular schwannoma (11 cases), meningioma (7 cases), glioma (7 cases), brain metastases (7 cases), hemangioblastoma (6 cases), cyst (1 case), and neuropathic conditions such as trigeminal neuralgia (43 cases), hemifacial spasm (22 cases), and glossopharyngeal neuralgia (1 case). All patients successfully underwent resection or biopsy of their lesions or microvascular decompression under full-neuroendoscopy. The follow-up period ranged from 3 months to 3 years. Enhanced MRI confirmed complete resection in 34 tumor cases (87.2%), near-total resection in 3 cases (7.7%), and biopsy in 2 cases (5.1%). Three deaths occurred during follow-up. Among the patients with vascular neuropathic diseases, two with trigeminal neuralgia experienced incomplete pain relief postoperatively. The resolution rates for hemifacial spasm and glossopharyngeal neuralgia were 100%. Postoperative complications occurred in 3 cases, with 2 cases of hydrocephalus that were managed with ventriculoperitoneal shunting, and 1 case of poor wound healing.Conclusion·Full-neuroendoscopic technique demonstrates potential in the surgical treatment of posterior cranial fossa lesions.